Ответы и объяснения

  • Участник Знаний
2011-03-13T13:16:56+00:00

2/sin2x=2/(2*cosx*sinx)=1/(cosx*sinx)=(cos^2x+sin^2x)/(cosx*sinx)=ctgx+tgx

 

эт первый

 

вот второй

 

int(cos(x)*dx/(sin(x)+5))=int(d(sin(x))/(sin(x)+5))=ln(sin(x)+5)+C
int(dx/(sin^2(x)*(ctg(x)+3)))=-int(d(ctg(x))/(ctg(x)+3))=-ln|ctg(x)+3|+C
int(arcsin(x)*dx)=arcsin(x)*x-int(x*d(arcsin(x)))=x*arcsin(x)-int(x*dx/sqrt(1-x^2))=x*arcsin(x)-1/2*int(d(x^2)/sqrt(1-x^2))=x*arcsin(x)+sqrt(1-x^2)+C
flemer
В первой строке, когда растрывала скобки 3 на sin^2(x) не домножила.
И если t=tg(x), то x=arctg(t)+pi*k, dx=dt/(1+t^2), без двойки